High Order Thinking Skills (HOTS) Analysis of Grade VIII Junior High School Students on the Subject of Preserving My Nation's Culture - Anilawati, Anilawati; Jatiningsih, Oksiana; Listyaningsih, Listyaningsih (International Journal of Emerging Research and Review, 2025)
Objective: This study aims to analyze the higher-order thinking skills (HOTS) of students of State Junior High School 15 Surabaya. in understanding and applying the material "Preserving My Nation's Culture" in the Pancasila Education subject. The main focus of this study is to evaluate the extent to which students can analyze, evaluate, and create solutions in the context of preserving local and national culture.  Method: This research uses a descriptive qualitative approach with data collection methods through classroom observations, interviews with teachers and students, and document analysis in the form of worksheets and student assignments. Data analysis techniques are carried out by data reduction, data presentation, and drawing conclusions. Result: The results of the study show that the majority of students are still at a low level of thinking (LOTS), with a tendency to only be able to mention forms of culture that need to be preserved without being able to link the importance of such preservation to national identity and cultural sustainability. Only a small number of students are able to analyze cultural problems in their surroundings and design creative solutions, such as digital culture campaigns or community projects. The contributing factors include a learning approach that is not yet contextual, minimal use of local culture-based media, and a lack of teacher training in designing HOTS-based learning. Novelty: This study lies in its focus on the integration of HOTS skills in cultural themes that are contextual and relevant to students' daily lives. In addition, this study offers a local cultural project-based learning model that can be replicated to strengthen character and love for the nation's cultural heritage.